Analysis Of Factors Determining Supply Chain Resilience: A Study Of The Manufacturing Industry In Indonesia In The Era Of Global Volatility - Andi Abrar Dirgahayu; Indra Yusba Permatasari; Suryanti Suryanti; Mahfudnurjamamuddin Mahfudnurjamamuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study analyzes the crucial determinant factors for enhancing Supply Chain Resilience (SCR) in Indonesia's manufacturing sector amidst the unprecedented era of Global Volatility (VUCA). The national manufacturing industry, which contributes significantly to the GDP yet remains heavily dependent on imported raw materials and is vulnerable to domestic logistical complexity, faces substantial risks from geopolitical tensions, macro-economic fluctuations, and technological disruptions. Traditional lean supply chain models have proven inadequate, making SCR an urgent strategic imperative for maintaining competitiveness and profitability. The main objective of this study is to identify the most effective determinant factors contributing to SCR development to ensure optimal resource allocation for companies. This research uses an explanatory quantitative approach, with data collection through structured questionnaires. Data analysis is performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test the relationships between five determinant constructs (Digital Capability/Visibility, Strategic Agility, Collaborative Relations, Redundancy & Diversification, and Government Policy Support) against Supply Chain Resilience (Y). Conceptual findings and preliminary analysis indicate that Visibility and Collaboration are fundamental proactive capabilities. Visibility, supported by technologies like IoT and big data analytics, is crucial for the Anticipation phase by providing real-time disruption signals from Tier-N suppliers. Conversely, Collaboration based on trust enables risk-sharing and rapid Adaptation, transforming fragmented supply chains into a cohesive ecosystem. Therefore, manufacturing companies are advised to prioritize investment in bridging the digital gap with lower-tier partners and strengthening relational capital to achieve sustainable resilience amidst global turbulence.